Bandwidth Extension of Speech Signals - Iser, Bernd; Schmidt, Gerhard; Minker, Wolfgang (Lecture Notes in Electrical Engineering, 2008)
Bandwidth Extension of Speech Signals provides discussion on different approaches for efficient and robust bandwidth extension of speech signals while acknowledging the influence of noise corrupted real-world signals. The book describes the theory and methods for quality enhancement of clean speech signals and distorted speech signals such as those that have undergone a band limitation, for instance, in a telephone network. Problems and the respective solutions are discussed in regards to different approaches. The different approaches are evaluated and robustness issues for a real-time implementation are covered as well. The book includes topics related to speech coding, pattern- / speech recognition, speech enhancement, statistics and digital signal processing in general.